Fluidic Simulation and Optimization of Microchannels for Retinal Vein Occlusion (RVO) by Using Fuzzy Technique - Afzal, Muhammad Javaid; Javaid, Farah; Ilyas Yasin, Muhammad; Tayyaba, Shahzadi; Waseem Ashraf, Muhammad (Scientific Inquiry and Review, 2023)
A microelectromechanical system (MEMS) is a diminutive machine having electronic and mechanical components with a size ranging from 20 µm-1 mm. In this present-day world, MEMS fabrication techniques have remodeled the conventional approaches towards system fabrication. Microfluidics is an eminent domain of MEMS in which small volumes of fluids are disciplined in micro-channels having dimensions in the submillimeter to achieve the desired outputs. Microfluidics have revolutionized the realm of compact system fabrication through preeminent inventions like lab-on-a-chip technology. Microchannels of various architectures are fabricated to employ microfluidic systems depending upon the required function of the device. In ophthalmology, Retinal Vein Occlusion (RVO) is an ailment in which small veins that take away blood from the human eye’s retina are blocked or fissured, causing vision loss. Therefore, in this study, four micro-channels with different architectures, namely, sinusoidal, U-shaped, spiral, and curvilinear, were simulated by using the fuzzy technique to investigate the optimization of fluids for the implantation process to fix the RVO elixir. The two most critical parameters in retinal vein flow rate and velocity were taken at the output for optimization. Hence, fuzzy fluidic simulation revealed that curvilinear micro-channels were the best fit for biomedical implantation to treat RVO malady.